Metaboreflex Activity is Attenuated by Transcutaneous Electrical Nerve Stimulation and Interferential Electrical Stimulation in Healthy Individuals - Chiappa, Gaspar Rogerio da Silva; Zago, Julio; Vieira, Paulo; Winter, Andre; Winter, André; Chiappa, Adriana; Rondinel, Tatiana; Santos, Francisco; Cipriano, Gerson; Silveira, Marcos (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
Background: Transcutaneous electrical nervous stimulation (TENS) and interferential electrical stimulation (IES) attenuates muscle metaboreflex by sympathetic nervous modulation. Objective: We tested the hypothesis that IES may be more effective than TENS to improves blood flow which may be linked to greater of deep tissue. Methods: Eleven health subjects were randomized to TENS (80 Hz, 150μs), IES (4000 Hz, ΔAMF=25 Hz) or sham stimulation group, during 30 minutes. The acute intervention was applied on stellate ganglion region (C7-T4). Results: Were measured metaboreflex activity by calf vascular resistance (CVR) and calf blood flow (CBF) and HRV during three times: rest, exercise (static handgrip) and postexercise circulatory occlusion (PECO+ and PECO-). At the exercise peak, compared with TENS and Sham, the IES group reduced CVR (36 ± 3 vs 43 ± 3; p<0.05) and increased CBF (p<0.01). Also, IES was associated with a greater reduction on the MMA (IES: 9 ± 2, TENS: 14 ± 4, Sham: 26 ± 5 units; p<0.01). Furthermore, the IES group had a higher reduction of LF/HF ratio during PECO- and PECO+ (p<0.05). Conclusion: The IES over the stellate ganglion region seems to have superior efficacy compared with TENS to attenuate metaboreflex activation and vasodilatory responses during exercise in healthy subjects.